2012
DOI: 10.1104/pp.112.201996
|View full text |Cite
|
Sign up to set email alerts
|

A Land-Plant-Specific Glycerol-3-Phosphate Acyltransferase Family in Arabidopsis: Substrate Specificity, sn-2 Preference, and Evolution    

Abstract: Arabidopsis (Arabidopsis thaliana) has eight glycerol-3-phosphate acyltransferase (GPAT) genes that are members of a plantspecific family with three distinct clades. Several of these GPATs are required for the synthesis of cutin or suberin. Unlike GPATs with sn-1 regiospecificity involved in membrane or storage lipid synthesis, GPAT4 and -6 are unique bifunctional enzymes with both sn-2 acyltransferase and phosphatase activity resulting in 2-monoacylglycerol products. We present enzymology, pathway organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
247
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(260 citation statements)
references
References 56 publications
6
247
1
6
Order By: Relevance
“…Indeed, the signature metabolites for suberin formation were also identified in the russeted apple surface. These included an increase of ferulates (Serra et al, 2010) and dicarboxylic fatty acids (Kolattukudy, 2001;Compagnon et al, 2009;Yang et al, 2012) and an increase in chain length of the modified FAs (Kolattukudy, 2001;Compagnon et al, 2009). Furthermore, large-scale expression analysis performed in both tomato and apple material confirmed the metabolic shift occurring in the suberized fruit surfaces, corresponding to the reduction in cutin polymer and its replacement with suberin.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the signature metabolites for suberin formation were also identified in the russeted apple surface. These included an increase of ferulates (Serra et al, 2010) and dicarboxylic fatty acids (Kolattukudy, 2001;Compagnon et al, 2009;Yang et al, 2012) and an increase in chain length of the modified FAs (Kolattukudy, 2001;Compagnon et al, 2009). Furthermore, large-scale expression analysis performed in both tomato and apple material confirmed the metabolic shift occurring in the suberized fruit surfaces, corresponding to the reduction in cutin polymer and its replacement with suberin.…”
Section: Discussionmentioning
confidence: 99%
“…S10A). Of particular note, the expression levels of CD3 and GLYCEROL-3-PHOSPHATE ACYLTRANSFEREASE6 (GPAT6), which catalyze cutin monomer formation (Shi et al, 2013;Yang et al, 2012), were significantly lower (2-to 4.5-fold) in the ABA-deficient mutants than in their respective wild-type genotypes (Supplemental Fig. S10A).…”
Section: Effect Of Aba Application On Aba-deficient Leavesmentioning
confidence: 99%
“…Interestingly, in vitro biochemical studies revealed that these GPATs catalyze the acyl transfer to the sn-2 position of glycerol in contrast to the classical GPAT-catalyzed sn-1 acylation (Yang et al, 2010). Therefore, an important branch point between membrane lipid synthesis and polyester synthesis may have evolved within the GPAT family (Yang et al, 2012). In addition, differences in the activity of the GPAT4/8 and GPAT5 are hypothesized to be critical for the synthesis of cutin and suberin; these enzymes are discussed in detail below (Yang et al, 2012).…”
Section: Acyl Transfer To Glycerol-3-phosphatementioning
confidence: 99%
“…Therefore, an important branch point between membrane lipid synthesis and polyester synthesis may have evolved within the GPAT family (Yang et al, 2012). In addition, differences in the activity of the GPAT4/8 and GPAT5 are hypothesized to be critical for the synthesis of cutin and suberin; these enzymes are discussed in detail below (Yang et al, 2012).…”
Section: Acyl Transfer To Glycerol-3-phosphatementioning
confidence: 99%